(untitled) (International Journal of Environmental Sciences, 2025)
Background: The global increase in mobile phone usage has raised public health concerns regarding prolonged exposure to electromagnetic radiation and its potential genotoxic effects. The oral mucosa, due to its close contact with mobile devices during calls, may be especially vulnerable. Conditions such as type 2 diabetes mellitus and iron deficiency anemia are already associated with increased oxidative stress and DNA damage, yet their interaction with mobile radiation remains poorly understood. The micronucleus (MN) assay serves as a reliable, non-invasive biomarker for identifying DNA damage in exfoliated buccal cells. Aim and Objectives: This study aimed to evaluate DNA damage by assessing the frequency of micronuclei in the buccal cells of three groups—healthy individuals, diabetic patients, and those with iron deficiency anemia—each using mobile phones for approximately 2 ± 1.5 hours daily. The objective was to compare MN frequency across the groups. Methods: A total of 180 participants aged 25–45 were categorized into three equal groups: Group I (healthy), Group II (diabetic), and Group III (anemic). Buccal cell smears were collected from the side predominantly used during phone calls, followed by Papanicolaou staining and evaluation under a light microscope using the criteria by Tolbert et al. Statistical analysis was performed using ANOVA and Spearman’s correlation coefficient. Results: The frequency of cells with micronuclei was significantly higher among diabetic (51.4%) and anemic subjects (37.8%) compared to healthy individuals (12%) (p < 0.001). Diabetics showed a very strong positive correlation between MN frequency and HbA1c levels (r = 0.999, p < 0.001), while anemics exhibited a strong negative correlation between MN frequency and serum ferritin (r = –0.626, p < 0.001). Healthy subjects demonstrated a moderate positive correlation between mobile phone usage duration and MN frequency (r = 0.646, p < 0.001). Conclusion: The study highlights a significant increase in DNA damage among diabetic and anemic individuals compared to healthy controls, suggesting that underlying systemic conditions amplify susceptibility to genotoxic effects. These findings underscore the need for careful monitoring of mobile radiation exposure, especially in individuals with chronic diseases.